The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/acs.inorgchem.9b00629
|View full text |Cite
|
Sign up to set email alerts
|

Side-Arm Functionalized Silylene Copper(I) Complexes in Catalysis

Abstract: A convenient new method was added to the toolbox of the ligand design of N-heterocyclic silylenes and their transition-metal complexes. Herein we report on six novel compounds of two novel classes of copper­(I) complexes based on the benzamidinate silylene (Cl)­Si­(PhC­(NtBu)2). By taming the high reactivity of the free electron pair of the Si­(II) atom via a preset metalation with a desired metal precursor (in this case copper­(I) halides) we can easily introduce novel pyridyl-based groups in the subsequent f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 87 publications
1
11
0
Order By: Relevance
“…Very recently, Stalke et al. synthesized a side‐arm functionalized silylene ligand and their transition metal complexes [10] . In 2014, Driess et al.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Stalke et al. synthesized a side‐arm functionalized silylene ligand and their transition metal complexes [10] . In 2014, Driess et al.…”
Section: Introductionmentioning
confidence: 99%
“…Some bidentate silylene ligands can constitute triangle centers with metals. [36] This phenomenon occurs for our scrutinized complexes of bidentate silylenes and rhodium (1 Table 1). The results indicate that by increasing the electron donating ability of substituents (NH 2 > OH > PH 2 > SH), the possibility of triplet ground state increases.…”
Section: Resultsmentioning
confidence: 83%
“…Some bidentate silylene ligands can constitute triangle centers with metals. [ 36 ] This phenomenon occurs for our scrutinized complexes of bidentate silylenes and rhodium ( 1 ′ Rh ‐ 4 ′ Rh ). All 1 Rh ‐ 4 Rh show rather same Si‐Rh bond length of 2.22 Å.…”
Section: Resultsmentioning
confidence: 94%
“…Transition metal (M) complexes containing HT ligands have been known for more than 40 years, however, the investigation of their applicability in the field of homogeneous catalysis is as yet in its initial stages,[2a], particularly in comparison with that of NHC complexes . Such a dissimilar situation is mainly a consequence of the generally lower stability of HT‐M complexes, since degradation reactions involving oxidation, hydrolysis and substitution processes are well known for systems of this kind.…”
Section: Introductionmentioning
confidence: 99%
“…Such a dissimilar situation is mainly a consequence of the generally lower stability of HT‐M complexes, since degradation reactions involving oxidation, hydrolysis and substitution processes are well known for systems of this kind. However, the last few years have witnessed the appearance of a family of bi‐ and tridentate ligands containing one or more HTs as donor groups that not only present significant catalytic activities in a number of organic transformations but have also shown that the HT groups play a steering role in the catalytic reactions. [2a] Figure presents the bi‐ ( I – IX ) and tridentate ( X – XI ) HT ligands whose transition metal complexes (or at least some of them) have already proven to be active catalysts (or catalyst precursors) in homogeneous catalysis.…”
Section: Introductionmentioning
confidence: 99%